C - reactive protein predicts proximal femur osteomyelitis in suppurative hip arthritis - Haiting Jia; Tao Liu; Jiazhi Yu; Mingzhu Lu (Journal of Orthopaedic Surgery and Research)
Abstract Background Ultrasound is capable of detecting hip joint effusion and guiding puncture procedures, which is cheap and convenient, but can not identify osteomyelitis. Magnetic resonance imaging (MRI) has high sensitivity and specificity for diagnosing osteomyelitis, but it is time-consuming and expensive. The purpose of this study was to find out certain indicators to identify suppurative hip arthritis with proximal femur osteomyelitis in order to optimize MRI. Methods Data of 48 children with acute suppurative arthritis of the hip diagnosed and treated from March 2018 to September 2024 were retrospectively analyzed. According to the results of MRI, 28 children with simple suppurative arthritis of the hip were included in the suppurative arthritis group, and 20 children with suppurative arthritis of the hip accompanied by osteomyelitis of the proximal femur were included in the osteomyelitis group. Age, sex, duration of onset, maximum body temperature at onset, and inflammatory indicators detected after admission were compared and analyzed between the two groups. The effectiveness of each index in diagnosing proximal femoral osteomyelitis was evaluated according to receiver operating characteristic (ROC). Logistic regression analysis was used to determine independent risk factors for proximal femoral osteomyelitis. Results There were no significant differences in age, sex, duration of onset, maximum body temperature, white blood cell count, neutrophil count and erythrocyte sedimentation rate between the two groups (P > 0.05). The median C-reactive protein was 31.58 mg/L and 76.69 mg/L in suppurative arthritis and osteomyelitis group, respectively, and the difference was statistically significant (P < 0.05). The sensitivity, specificity and area under the ROC curve of C-reactive protein were 80.0%, 67.9% and 0.770, respectively. Logistic regression analysis showed that C-reactive protein > 47.04 mg/L (OR = 8.444, 95%CI: 2.184–32.658) was an independent risk factor for predicting proximal femoral osteomyelitis (P < 0.05). Conclusions Compared with simple suppurative arthritis of the hip, C-reactive protein was higher in suppurative hip arthritis with osteomyelitis of the proximal femur. C-reactive protein > 47.04 mg /L can predict the possibility of suppurative hip arthritis accompanied by proximal femur osteomyelitis, and it is recommended that such children should undergo MRI in time.